Radiotherapy plus immune checkpoint inhibitors versus immune checkpoint inhibitors alone for non-small cell lung cancer with bone metastases: a systematic review and meta-analysis of comparative cohort studies - Ruan, Yingding; Cao, Wenjun; Long, Chuan; Guo, Siyu; Han, Jianwei; Chen, Zhendong; Zhang, Ting (Frontiers in Immunology, 2026)
BackgroundBone metastases are a frequent and clinically consequential complication of advanced non-small cell lung cancer (NSCLC), associated with substantial morbidity and poor survival. Whether adding radiotherapy (RT) to immune checkpoint inhibitors (ICIs) improves outcomes remains uncertain.MethodsWe searched PubMed, Cochrane Library, Web of Science, Scopus, and Embase (January 2010–October 2025) for comparative studies of RT + ICI versus ICI alone in patients with NSCLC and radiologically or pathologically confirmed bone metastases. Primary outcomes were overall survival (OS) and progression-free survival (PFS); secondary outcomes were objective response rate (ORR), grade ≥3 adverse events (AEs), and skeletal-related events (SREs). Study quality was assessed using the Newcastle–Ottawa Scale. Hazard ratios (HRs) were pooled for time-to-event outcomes and odds ratios (ORs) for binary outcomes, using fixed- or random-effects models according to heterogeneity.ResultsSix studies (n = 1,631) were included. RT + ICI improved OS (HR 0.58, 95% CI 0.44–0.76; I² = 68%) and PFS (HR 0.44, 95% CI 0.37–0.53; I² = 0%) versus ICI alone. The OS benefit persisted after excluding the large database cohort (HR 0.52, 95% CI 0.42–0.63). ORR was not significantly different (OR 1.68, 95% CI 0.77–3.66; I² = 74%), and grade ≥3 AEs were comparable (OR 1.00, 95% CI 0.78–1.27; I² = 0%). RT + ICI reduced SREs (OR 0.16, 95% CI 0.04–0.68; I² = 0%), but this estimate is based on sparse events.ConclusionsLow- to moderate-quality observational evidence suggests that RT combined with ICIs may be associated with improved survival without an apparent increase in severe toxicity in NSCLC with bone metastases. Any apparent reduction in SREs should be interpreted cautiously given the sparse event data. Prospective phase III randomized trials are needed to confirm causality and refine patient selection.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251230736.